Innovation and knowledge creation in an open economy Canadian industry and international implications - Baldwin, John R. 1945- (Cambridge University Press, 2003)
This study of innovation - its intensity, the sources used for knowledge creation, and its impacts - is based on a comprehensive survey of innovation of Canadian manufacturing firms. Attention is paid to the different actors in the system, who both compete with and complement one another. The study investigates how innovation regimes differ across size of firm and across industries. Owing to the high degree of foreign investment in Canada, special attention is paid to the performance of foreign-owned firms. The innovation regime of Canadian innovators is compared with results of studies of other industrialized countries. The picture of a typical innovator is a firm that combines internal resources and external contacts to develop a set of complementary strategies. The study finds that innovating firms depend not only on R&D, but also on ideas and technology from various other sources, both internal and external to the firm